Efficacy of remote telemetry data loggers for landscape‐scale monitoring: A case study of American martens. (3rd September 2016) - Sirén, Alexej P. K.; Maynard, Daniel S.; Kilborn, Jillian R.; Pekins, Peter J.
ABSTRACT: Remote telemetry data loggers are commonly used for monitoring wildlife species. Although remote telemetry data loggers provide reliable microhabitat use data, few studies have used them to evaluate landscape‐scale, temporal, and spatial habitat use. We installed 3 data loggers along a mountain ridgeline that was being developed for a commercial wind farm in northern New Hampshire, USA, to monitor use of a high‐elevation forest by American martens ( Martes americana ). We tested 1) the efficacy of data loggers to record presence–absence and index space use in a 6.75‐km 2 area, validating marten locations using radiotelemetry and camera traps; and 2) whether there were diel and seasonal biases of data logger detections. As a case study, we evaluated temporal and spatial habitat‐use hypotheses with respect to variations in vegetation cover (leaf‐on or leaf‐off) and astronomical seasons using data from 11 martens monitored for nearly 2 years (6 Feb 2011–23 Dec 2012). Data loggers recorded presence–absence of radiocollared martens across 80% (240 of 299) of the trials within the study area with few false positives (4%; 19 of 494 trials). Detection probability and spatial use were most influenced by elevation, distance to data loggers, and line‐of‐sight view. We did not detect a seasonal bias but data loggers recorded fewer nocturnal detections. We recorded 118, 120 detections of radiocollared martens, most of which occurred during leaf‐off seasons (87%; 102, 931). Spatial use declined significantly (β = −0.54, P = 0.04) during the first leaf‐on season, corresponding with the construction phase of the wind farm project, and remained lower throughout the study. Diel use was explained by an astronomical calendar with greater nocturnal use during autumn and winter. Our results show that remote telemetry data loggers provided accurate spatiotemporal data for landscape‐scale habitat monitoring, overcoming many of the problems with telemetry data—such as limited sampling period and bias—that can compromise measurements of space use. We suggest incorporating remote telemetry data loggers for space use and disturbance studies of wildlife species. © 2016 The Wildlife Society. Abstract : Our study showed that data loggers can effectively monitor landscape‐scale habitat use of small mammal (<2.5 kg) populations. We evaluated high‐elevation habitat use of a local American marten ( Martes americana ) population as a case study and recorded seasonal shifts to high‐elevation forest during leaf‐off seasons with the lowest use during wind farm construction.